2022
DOI: 10.36253/phyto-13357
|View full text |Cite
|
Sign up to set email alerts
|

Recovery after curettage of grapevines with esca leaf symptoms

Abstract: Grapevine curettage was re-introduced in France in the early 2000s, and is important for facilitating recovery of plants from esca disease. This surgical practice involves removal of deadwood of vines with leaf symptoms, focusing on white rot generally observed at the centres of grapevine trunks. Assessment of the efficacy of this practice was initiated in the Bordeaux region in 2014. One ‘Sauvignon Blanc’ vineyard severely affected by esca was initially surveyed in the summer of 2014, to identify and treat vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
(44 reference statements)
1
19
0
Order By: Relevance
“…the use of certain rootstocks or types of pruning) may be specific to a particular cultivar and wine region. Such factors are known to affect susceptibility to esca (Lecomte et al 2018). It was not possible to investigate these confounding factors here, but the observed differences in esca incidence between the cultivars studied here were correlated with the range of susceptibility of the same cultivars quantified over several years in a common garden vineyard (Gastou et al 2024).…”
Section: Discussionmentioning
confidence: 99%
“…the use of certain rootstocks or types of pruning) may be specific to a particular cultivar and wine region. Such factors are known to affect susceptibility to esca (Lecomte et al 2018). It was not possible to investigate these confounding factors here, but the observed differences in esca incidence between the cultivars studied here were correlated with the range of susceptibility of the same cultivars quantified over several years in a common garden vineyard (Gastou et al 2024).…”
Section: Discussionmentioning
confidence: 99%
“…In viticulture, intensive pruning schemes (e.g. spur or cane pruning), can cause more frequent external FTD symptoms than minimal pruning schemes (Lecomte et al, 2018(Lecomte et al, , 2022Kraus et al, 2019). It was also assumed that intensive pruning causes more and larger pruning wounds on grapevine trunks, leading to increased infections by wood degrading fungi, and consequent interruption of host vascular systems and increased symptoms (Travadon et al, 2016;Kraus et al, 2022).…”
Section: Crop Intensificationmentioning
confidence: 99%
“…Esca wood symptoms include black spots in trunk crosssections and streaking in longitudinal sections but can be surrounded by pink to brown wood discolorations, and in older vines, white rot is also common. Foliar symptoms associated with esca include tiger stripe leaf patterns, wilting, and apoplexy, ranging from a few leaves to the entire vine canopies (Mugnai et al, 1999;Surico, 2009;Lecomte et al, 2012;Lecomte et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Wood dieback symptoms caused by Eutypa and Botryosphaeria were less frequently recorded, although incidence of Botryosphaeria canker was reported to be increasing in several countries. In France, the National Grapevine Trunk Disease Survey reported that GTDs incidence increased nationally from 3 to 13% between 2003 and 2013, with esca being the most-widespread, whereas other GTDs such as Eutypa dieback were more region-specific (Fussler et al, 2008;Bruez et al, 2013;Lecomte et al, 2018). Esca foliar symptom expression has been shown to be erratic, linked to different amounts of annual rainfall, particularly in late spring to early summer (Calzarano et al, 2018;Kraus et al, 2019;Dewasme et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation